Advancing One Health by Integrating Veterinary and Human Vaccines to Address Global Health Challenges - Pino, María Teresa Luján (2025)
The increasing frequency of zoonotic outbreaks calls for stronger integration between human and animal health sectors under the One Health framework. Veterinary vaccinology plays an important role in pandemic preparedness and control, demonstrated by how immunization strategies targeting animals—such as dog vaccination for rabies or livestock vaccination for Rift Valley fever—have directly reduced human disease burden. Moreover, veterinary medicine has served as a platform for vaccine innovation, contributing technologies like viral vectors, oil-based adjuvants, and thermostable formulations now applied in human vaccines. Transboundary animal diseases, even when not directly zoonotic, pose risks through ecological disruption and human-animal interface, impacting the economy and reinforcing the need for coordinated surveillance and immunization strategies. Collaborative efforts that bring together veterinary and human health sectors can strengthen disease control, improve research outcomes, and promote fairness in resource-limited environments. Greater medical engagement in One Health is essential to prevent future epidemics and safeguard public health globally.